KOMPETENSI, MOTIVASI DAN KOMITMEN TERHADAP KEMAJUAN ORGANISASI MELALUI KINERJA PEGAWAI - Sitti Nurbaya (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to analyze the influence of competence, motivation and commitment to organizational progress through employee performance. This type of research is survey research with a quantitative approach with an inferential research type. The population was 11,143 and the sample technique using Slovin by determining a random sample of 5% was obtained by 386 respondents. Quantitative research approach with primary and secondary data sources. Data collection using direct observation instruments and questionnaire dissemination. Data analysis using inferential analysis with descriptive statistics and computer-assisted Structural Equation Modeling (SEM) analysis using AMOS 5.0 and SPSS version 20.0 program packages. The results of the study found that competence and commitment have a direct and indirect relationship and influence that has a positive and significant impact on organizational progress through employee performance. The role of competence and commitment contributes to realizing organizational progress through individual performance, both in quantity, quality, efficiency, effectiveness and loyalty. Through performance has a positive and significant influence on the progress of the organization according to work orientation, perspective, totality, integrity, innovation and transformation. While motivational variables either directly or indirectly influence the progress of the organization through performance. The novelty of this research finding is